Diferenciações na produção siderúrgica e implicações para o desenvolvimento na Amazônia Oriental Brasileira - LOIOLA, Edney (Universidade Federal do Pará, 2014)
Strategies for upgrading Amazon designed by the national government had in its proposed guidelines the fragile geopolitical security and regional development, focused centrally for the installation of industrial enterprises, among them the independent steel companies, under the notion that this activity going on would for the production of steel products and so it is to be regional development. By analyzing the differences of production routes independent, integrated and semi-integrated is possible to understand how the elements of industrial plants behave in each route and how they interrelate with the regional socioeconomics. The research work with the pig iron has identified that the independent installation of steel and in the towns of Marabá (PA) and Açailândia (MA) generated unfulfilled expectations of local development, strengthening, therefore, only as an activity that allowed for economic growth, it maintained a production route that articulated the activity with the regional socio-economy in fragile and unsustainable foundations, supported mainly on the demand for charcoal. The cost structures and structural elements of each route identified the differences that each route has, especially in the relationship maintained with the regional economy because it involves new processes, technologies and differentiated products. The logic-based independent production of steel in the transfer and externalization of costs to society, labour relations and limited environmental degradation, without, however, establishing innovation processes led to the failure to establish procedures for the development of local base. The prospect of integrated steel production routes and semi-integrated that settle in the Amazon have no basis to change the scenery and regionally designed to transform the relationships maintained by an independent steel industry in the eastern Amazon, since they interconnect elements that contribute to the consolidation effects backward chaining and forward.